Corporatization of public services. (17th April 2022) - Andrews, Rhys; Clifton, Judith; Ferry, Laurence
Abstract: The corporatization of public services by moving services previously provided in‐house into various types of arms‐length corporate forms of organization is becoming an important trend at multiple levels of government. Although the use of such corporate forms to deliver public services is not a new phenomenon, evidence on the impact of corporatization on public services provision is only slowly emerging. In this symposium, we aim to advance our understanding of the theoretical and practical implications of corporatization through empirical analyses of its dynamics in a range of different settings. In this introductory article, we begin by explaining what is meant by the corporatization of public services and the different forms that it can take, before summarizing the existing evidence on the governance, accountability, and performance of corporatized public services. We then describe the articles included in the symposium and conclude by outlining a future research agenda for studying corporatization.